Ayurvedic Management of Dushta Vrana (Varicose Ulcer) with Dashanga Lepa (International Journal of Ayurveda and Pharma Research, 2024)
A wound, also known as a Vrana, is a condition where the body's tissues are damaged in a specific way, and after repair, the tissues become discolored, resulting in a permanent scar. Varicose ulcers are caused by persistent venous occlusion. A varicose leg ulcer occurs when blood recirculates through venous valves due to ischemia in the leg's vascular supply, caused by this insufficiency. Ignoring these lesions could lead to gangrene and infection. According to Ayurveda, varicose ulcers are associated with 'Sira Janya Dusta Vrana.' In the medical field, "Lepa" can be described as a therapeutic approach where medications are applied externally to alleviate pain, reduce inflammation, or speed up recovery. This case report on varicose ulcers includes the patient's complete medical history, necessary laboratory tests, and clinical and physical examinations. The patient undergoes daily dressings on an OPD basis and is treated with various internal medications along with external procedures like the application of Lepa. After the administration of Lepa, the wound healed, and other symptoms improved significantly.